RESPON EKSPLAN DUKU (Lansium domesticum Corr.) TERHADAP PEMBERIAN AUKSIN DAN SITOKININ DALAM MEDIUM MURASHIGE AND SKOOG - Agung Prassetio; Fetmi Silvina; Murniati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aimed to know the response of Duku explants toward the giving of auxin (2,4-D) and cytokinin (BA) for callus growth. This research was conducted in plants biotechnology laboratory at University of Riau, from January until May 2014. The experimental design used was randomized block design (RBD) which is consisted by 2 factors. First factor is the giving of 2,4-D concentration consisting by 3 levels, they are: A1 = 1 mg 2,4-D/l, A2 = 1.5 mg 2,4-D/l and A3 = 2 mg 2,4-D/l. Second factor is the giving of BA concentration consisting by 3 levels, they are: B1 = 0 mg BA/l, B2 = 0.5 mg BA/l and B3 = 1 mg BA/l. This research observed visually and represented by image. Results of this research showed the duku explant that inoculated with 1-2 mg/l of auxin (2,4-D) concentration and cytokinin (BA) 0-1 mg/l or by giving of the both combinations still not make the callus growth, because half of the explant turning brown and finally die.   Keyword: duku, 2,4-D, BA, in vitro, brown